Conservation of Endemic Birds Through the Willingness to Pay Tourists in the Manusela National Park Eco-Tourism Area - Latupapua, Yosevita Th.; Soselisa, Fanny (Media Konservasi, 2024)
Ecotourism management requires a lot of funds, so through ecotourism activities visitors can get involved in supporting the conservation of the area through willingness to pay (WTP). The purpose of this study was to determine the perceptions and preferences of tourists and the willingness to pay visitors (WTP) in supporting the conservation of typical bird species in MNP. Determination of the sample using accidental sampling technique. The number of samples used was 38 tourists. The characteristics and perceptions of visitors were analyzed using qualitative descriptive, while the willingness to pay of tourists used quantitative analysis. The results showed of the calculation WTP to support the conservation of endemic bird species through the management of birdwatching ecotourism attractions obtained a value of 2,000 000, -. This value indicates that the appropriate price for birdwatching ecotourism services in Masihulan Village for tourists is 2,000,000,-.